ANALYSIS OF THE APPLICATION OF THE ENVIRONMENTAL MANAGEMENT SYSTEM BASED ON STANDARDS IN THE INTERNATIONAL REQUIREMENTS OF ISO 14001 - Fajar Ramadhan Kojra; Sukanta Sukanta; Kusnadi Kusnadi (Department of Environmental Engineering - Universitas Pasundan - Indonesia, 2020)
The environment is one of the important factors in the success of an industrial company. This triggers the company to improve overall performance to implement a better environmental management system. ISO 14001 is an international standard that can be applied by companies to maintain and improve environmental management systems. This study aims to analyze the application of environmental management systems at PT. XYZ and know how far the company is ready to implement ISO 14001. The method used in this study is the Self Assessment Checklist for assessing clauses at ISO 14001. Data collection is done by observing the study site and conducting interviews with employees to obtain information at the company. Data processing is done by assessing the ISO 14001 clause with a self assessment checklist. The results of this study note that the value of the company's readiness to implement an environmental management system based on ISO 14001 standards is equal to 50.41% with a weak category.